Answer:
y = 3x + 2
Step-by-step explanation:
Let's identify two clear points on this line. I can see (0, 2) and (-1, -1)
First you want to find the slope of the line that passes through these points. To find the slope of the line, we use the slope formula: (y₂ - y₁) / (x₂ - x₁)
Plug in these values:
(-1 - 2) / (-1 - 0)
Simplify the parentheses.
= (-3) / (-1)
Simplify the fraction.
-3/-1
= 3
This is your slope. Plug this value into the standard slope-intercept equation of y = mx + b.
y = 3x + b
To find b, we want to plug in a value that we know is on this line: in this case, I will use the first point (0, 2). Plug in the x and y values into the x and y of the standard equation.
2 = 3(0) + b
To find b, multiply the slope and the input of x(0)
2 = 0 + b
Now, we are left with 0 + b.
2 = b
Plug this into your standard equation.
y = 3x + 2
This is your equation.
Hope this helps!
Answer:
A) CPCTC
Step-by-step explanation:
This part of the proof occurs right after two triangles are proven congruent. One could now conclude and establish that every part of each congruent triangle is congruent, which is what is most likely happening in this scenario.
Answer is (A). For a term with an irreducible
![n](https://tex.z-dn.net/?f=n)
-degree polynomial in the denominator, its numerator must have at most a polynomial of degree
![n-1](https://tex.z-dn.net/?f=n-1)
.
Replace each letter for the value it's worth, so:
= 10 * -4 * 5
= -200